Uncovering mechanism of hepatotoxicity diseases caused by tetrahydrocannabinol based on novel network toxicology and experimental verification - Tiantian Zou; Ruilin Zhang; Liping Hu; Genmeng Yang; Xuanyu Chen; Mengqing Wang; Tiantian Cheng; Shengjie Nie; Linlin Liu; Shijun Hong (Scientific Reports)
Abstract This study systematically investigated the molecular mechanisms underlying tetrahydrocannabinol (THC)-induced hepatotoxicity in humans through an integrated approach combining network toxicology, molecular docking, and experimental validation. Our analysis identified 22 core targets associated with THC-mediated hepatotoxicity. Protein-protein interaction (PPI) network analysis revealed significant functional associations among these 22 potential target proteins. KEGG pathway and GO term analyses demonstrated that THC potentially exerts hepatotoxic effects through multiple biological processes, including endocrine resistance, bile secretion, negative regulation of apoptosis, and cellular oxidant detoxification. Disease enrichment analysis further identified several pathological conditions closely associated with THC-induced hepatic damage. Molecular docking simulations demonstrated strong binding affinities between THC and functional domains of 17 target proteins that participated in the aforementioned enriched pathways. An in vitro model of THC-induced hepatocyte injury was successfully established and subsequently validated through RT-qPCR experiment. THC exposure significantly altered the expression patterns of 10 critical target genes: ERBB2, GPX1, MAPK14, NR1H4, SOD1, CXCR2, PPARG, EGFR, TYMS and KDR. The hepatotoxic effects of THC appear to arise from the synergistic interplay of multiple pathways and the coordinated dysfunction of various gene products. These findings elucidate key molecular pathways and therapeutic targets associated with THC-induced hepatotoxicity, providing a theoretical foundation for developing clinical interventions and hepatoprotective strategies against cannabis-related liver damage.